The English language teacher's handbook : how to teach large classes with few resources - Baker, Joanna; Westrup, Heather (London : Continuum, 2000)
Introduction. Introducing change. Background to teaching English. Organising lessons to teach new language. Organising lessons to improve language skills. Ideas for reaching vocabulary. Ideas for teaching grammar...
Keywords: English language; Foreign speakers; English language -- Study and teaching -- Foreign speakers